Teaching coherent descriptive speech to children of senior preschool age with speech underdevelopment problems - L. G. Shadrina; O. V. Efimova (Russian State Vocational Pedagogical University, 2020)
Introduction. Today, one of the main requirements of the Federal State Educational Standard of Preschool Education is to ensure the speech development in children, which means mastering them of free, coherent dialogue and monologic speech skills as a means of communication with adults and peers. The indicators of successful speech development are skills to build different types of coherent statements. This requirement fully applies to children with minor speech delays. However, in modern speech therapy, the development of coherent speech is made dependent on the elimination of the shortcomings of unformed language structures and involves the use of reproductive techniques, including mainly constant repetitions of speech patterns. Children are simply asked to copy stereotypical schemes when making their own statements, but the attention is not paid to the process of formulating rules and peculiarities of description texts, the understanding of which is very important to be prepared for school. Thus, it is significantly important to revise well-established techniques to learn oral monologue speech when teaching children with serious speech disorders.The aim of the present article is to discuss the conditions for effective development of coherent descriptive speech in preschool children with speech underdevelopment problems.Methodology and research methods. The methodological framework of the research is based on the theory of speech activity and the theory of developmental education, as well as the systematic analysis of the peculiarities of verbal communication skills in children and modern ideas of correctional pedagogy about the structure of speech defects. In the course of the research, empirical research methods and a pedagogical experiment were employed.Results and scientific novelty. Children aged 5-6 years old (n = 60) with the logopedic report "general underdevelopment of speech of the 3 rd -4 th levels" took part in the experimental research. It was proved that it is necessary to teach preschool children with speech disorders not only to speak by analogy and model structures, but also to formulate detailed meaningful descriptive statements. The entry test demonstrated that most respondents have insufficient formation of coherent descriptive speech: 40% - medium level, 38% - low level. More than half of preschool children in the experimental group (53,6%) improved their results through the targeted and comprehensive correctional work, in the course of which they learned practical description skills. While working on description skills, children learned how to highlight and compare essential features of a subject, to combine individual phrases into a consistent message. The priority areas were identified in each speech task to ensure the greatest impact of its performance. The conducted classes influenced not only speech, but also cognitive development of children. Also, the classes stimulated children's speech and thought activities, contributed to the activation of visual, auditory and tactile perception, memory, attention and observation.Practical significance. The research materials provide a new direction to determine the technologies for the development of coherent speech in children of senior preschool age with speech underdevelopment.